Chlorogenic acid improves ex vivo vessel function and protects endothelial cells against HOCl-induced oxidative damage, via increased production of nitric oxide and induction of Hmox-1 - Jiang, R.; Hodgson, J.; Mas, E.; Croft, K.; Ward, Natalie (Elsevier Inc., 2016)
Dietary polyphenols are potential contributors toward improved cardiovascular health. Coffee is one of the richest sources of dietary polyphenols in a coffee-drinking population, the most abundant form being chlorogenic acid (CGA). Endothelial dysfunction is an early and major risk factor for cardiovascular disease. Nitric oxide (NO) is a key factor in regulation of endothelial function. Heme oxygenase-1 (Hmox-1), an inducible isoform of heme oxygenase that is produced in response to stressors such as oxidative stress, may also play a role in vascular protection. The aim of this study was to investigate the effect of CGA on endothelial function with oxidant-induced damage in isolated aortic rings from C57BL mice. We further examine the mechanism by investigating cell viability, activation of eNOS and induction of Hmox-1 in human aortic endothelial cells (HAECs). We found that pretreatment of isolated aortic rings with 10-μM CGA-protected vessels against HOCl-induced endothelial dysfunction (P<0.05). Pretreatment of cultured HAECs with 10-μM CGA increased endothelial cell viability following exposure to HOCl (P<0.05). Moreover, CGA increased NO production in HAECs in a dose-dependent manner, peaking at 6 h (P<0.05). CGA at 5 μM and 10 μM increased eNOS dimerization at 6 h and induced Hmox-1 protein expression at 6 h and 24 h in HAECs. These results are consistent with the cardiovascular protective effects of coffee polyphenols and demonstrate that CGA can protect vessels and cultured endothelial cells against oxidant-induced damage. The mechanism behind the beneficial effect of CGA appears to be in part via increased production of NO and induction of Hmox-1.